THE INFLUENCE OF CUSTOMER ORIENTATION AND MARKETING INNOVATION TOWARDS SME’S PERFORMANCE IN EAST COAST MALAYSIA: A PROPOSED CONCEPTUAL MODEL - Najdah Abd Aziz; Rusnah Ismail; MA. Irfan Rahmana; Mulyana (International Journal of Accounting, Finance and Business, 2020)
SME is one of the government's initiatives to reduce the poverty rate in Malaysia and reduce the income gap between the rural and urban population. Therefore, entrepreneurs play an important role in managing the business as well as improving business income and performance. There have a few indicators in measuring the business performance. Thus, this study conducted to identify the influence of customer orientation and marketing innovation towards SME’s performance. A conceptual framework is developing to give a clear picture on the area study. A set of questionnaires distribute to 300 SMEs entrepreneurs randomly in East Coast Malaysia. Then data collected will analyse using SPSS version 24.